MEKANISASI PENYIAPAN LAHAN UNTUK UBIKAYU (THE MECHANIZATION IN LAND PREPARATION FOR CASSAVA) - triatmodjo, mochamad chaerudin (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
The Mechanization  in land preparation of   cassava cultivation was studied by survey method. In the modern custom there are full used of agricultural machinery which one of them is the farm mechanization by using farm tractor equipped with disc plow and ridger for ldaya and preparation of cassava plantation. The choose of agrticultural machinery should consider the technical and economical value and the culture of the farmer themselves. The economical analysis shows that One farm tractor 70 HP and the new price about 700 million rupiah should prepare about 750 hectars  of land for a year. The true analysis of technical and economical in the application of farm machinery would increase the total revenue and benefit of cassava cultivation. Key Words : Farm Tractor, Cassava, Agricultural machinery, Survey method.